Overturning Axis Selection in Curved Box-Girder Bridges with Single-Column Piers. (15th May 2018) - Song, Guohua; Che, Delu; Li, Minghui
Abstract : This study was conducted to theoretically analyze the overturning axes of curved box-girder bridges with three equal spans and single-column piers per the influence of curvature radius and bearing eccentricity on overturning axis. The theoretical analysis is verified by a model bridge experiment. The results show that overturning axis can be effectively determined according to the connecting line of either bearings at the central piers or outmost bearings at abutments as influenced by curvature radius and bearing eccentricity. In other words, no bearings are outside of overturning axis. All the bearings but the two on the overturning axis are located on the inner side of the axis. For curved bridges with multispans and single-column or double-column piers, the overturning axis is characterized by the connecting line of the two adjacent outmost bearings.